The Validity and Practicality of Student Worksheet Based on Guided Discovery to Practice Integrated Science Process Skills in Class XII Enzyme Submaterials - Sausan Dina Abidah; Yuliani Yuliani (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2020)
Science process skills are overall scientific skills that can be used to find a concept or theory. One method to train the learning process of students is through the guided discovery learning method. Guided discovery-based learning can be applied using student worksheet which is oriented towards scientific discovery activities. This study was designed to produce valid and practical student worksheet based on guided discovery to train integrated science process skills in Enzyme Sub materials. The study was conducted in October 2019 to March 2020 in the Biology Department, Faculty of Mathematics and Natural Science, State University of Surabaya. The type of this research is development research using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). At the time of analysis, it is done by analyzing the curriculum, students, concepts, and assignments. The design stage is completed with designing the student worksheet which is adapted to the syntax of the guided discovery. Further development (including) development, review, and revision, as well as validation of the student worksheet. Later the evaluation (Evaluation) of the validation results will be analyzed and evaluated. Validity is the feasibility of student worksheet which is determined by three validators given by lecturers of materials, education teachers, and high school biology teachers. The validity of the student worksheet was reviewed in terms of content validity, presentation, language, the suitability of the guided discovery method, and integrated science process skills. The method used in this study is the questionnaire method, validation method, and readability test. The instruments used were validation sheets and readability test sheets. Data analysis in the form of descriptive qualitative. The results showed that the guided discovery student worksheet was declared empirically feasible for use in XII high school students, and was declared valid with an average score of validation results of 3.81 with a very valid category and can be used in the learning process. Keywords: student worksheet validity, guided discovery, integrated science process skills, enzyme.